2002
DOI: 10.3171/jns.2002.96.6.1094
|View full text |Cite
|
Sign up to set email alerts
|

Heme oxygenase-1 gene therapy for prevention of vasospasm in rats

Abstract: These results show that overexpression of HO-1 inhibits arterial contractions induced by hemoglobin and can reduce vasospasm after experimental SAH.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
62
0

Year Published

2003
2003
2009
2009

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(63 citation statements)
references
References 51 publications
1
62
0
Order By: Relevance
“…It is interesting to note that one of the major pathological complications following such a haemorrhage is ischaemia brought on by delayed vasospasm (23). The vasoactive F 2 -isoprostanes have also been identified in the cerebrospinal fluid following haemorrhaging (24,25). The presence of Mb-X in the urine of patients diagnosed with rhabdomyolysis and the presence of Hb-X in the cerebrospinal fluid of patients with suggests that these haem proteins are a major driving force of lipid oxidation reactions and hence may be important in understanding the mechanisms of pathological complications.…”
Section: Introductionmentioning
confidence: 99%
“…It is interesting to note that one of the major pathological complications following such a haemorrhage is ischaemia brought on by delayed vasospasm (23). The vasoactive F 2 -isoprostanes have also been identified in the cerebrospinal fluid following haemorrhaging (24,25). The presence of Mb-X in the urine of patients diagnosed with rhabdomyolysis and the presence of Hb-X in the cerebrospinal fluid of patients with suggests that these haem proteins are a major driving force of lipid oxidation reactions and hence may be important in understanding the mechanisms of pathological complications.…”
Section: Introductionmentioning
confidence: 99%
“…( 11 ) reported a case of human HO-1 deficiency associated with endothelial cell injury, vulnerability to stress, anemia, and growth retardation. Conversely, experimental HO-1 gene delivery has been shown to result in amelioration of atherosclerosis ( 12 ), injury-induced vascular neointima formation ( 13 ), ischemic heart disease ( 14 ), renal ischemia/ reperfusion injury ( 15 ), hypoxia-induced lung injury ( 16 ) and liver ischemia/reperfusion injury ( 17 ), as well as improvement of vascular function ( 18 ).…”
Section: Introductionmentioning
confidence: 99%
“…Although the present results suggest that gene transfer driven by the enhanced GFAP promoter may be a useful tool for in vitro experiments, its efficacy in vivo remains to be defined. Precedent for therapeutic gene transfer using a viral vector in CNS hemorrhage models has been provided by Ono et al, who observed that adenoviral transfer of the HO-1 gene attenuated basilar artery vasospasm in a rat model of subarachnoid hemorrhage (Ono et al, 2002). In addition, Masada et al reported that intraventricular injection of an adenovirus encoding interleukin-1 receptor antagonist attenuated tissue edema and the local inflammatory response after experimental striatal hemorrhage (Masada et al, 2001).…”
Section: Discussionmentioning
confidence: 99%